ACUTE TONSILLITIS IN CHILDREN: A PEDIATRICIAN'S PERSPECTIVE - A. D. Vetrova (Union of pediatricians of Russia, 2014)
This article is dedicated to one of the most widespread pathologies in children - acute tonsillitis, which is a daily routine for both otolaryngologists and pediatricians. The authors analyze etiology and morphology of acute tonsillitis in children of various age groups. They revealed that the main complaint of pediatric patients is a sore throat. The authors present modern approaches to diagnostics and treatment of acute tonsillitis induced both by Group A β-hemolytic streptococcus and various viruses. In this article, they consider the possibility of using local treatment to treat inflammatory oropharyngeal diseases in combination with systemic antibacterial drugs and as monotherapy of acute throat pain. The authors substantiate use of throat lozenges with antiseptic and analgesic effects. They note effectiveness, safety and pharmacoeconomic advantages of a local antiseptic, anti-viral and anti-fungal drug. These aspects are of utmost importance to the choice of an antiseptic given that it is a non-prescription drug.